Pengaruh Keselamatan Kerja, Kepemimpinan, dan Disiplin Kerja terhadap Kinerja Karyawan di PT. Seven Clean Seas Batam - Dwi Novita Intan Nasari; Yandra Rivaldo; Hutri Agus Romi (Institut Nalanda, 2026)
This study aims to examine the effect of occupational safety (X1), leadership (X2), and work discipline (X3) on employee performance (Y) at PT. Seven Clean Seas Batam. A quantitative research design was employed using a survey method, with purposive sampling applied to select 54 respondents who met the study criteria. The data were analyzed using multiple linear regression to test the partial and simultaneous effects of the independent variables on employee performance. The findings indicate that partially, occupational safety (X1) has a significant positive effect on employee performance, with a significance value of 0.027 (< 0.05), while leadership (X2) does not show a significant effect, with a significance value of 0.786 (> 0.05). Work discipline (X3) has a strong and significant effect on employee performance, with a significance value of 0.000 (< 0.05). When analyzed simultaneously, occupational safety, leadership, and work discipline together significantly influence employee performance (F = 134.284, sig. 0.000 < 0.05). The coefficient of determination (R²) is 0.890, indicating that 89% of the variation in employee performance can be explained by these three factors. This study emphasizes the importance of enhancing occupational safety and work discipline to improve employee performance, while leadership should be further investigated for its indirect or moderating effects.